Urban megaprojects a worldwide view - Cerro Santamaría, Gerardo del (Emerald, 2013)
The aim of this book is to understand the causes and consequences of new scales and forms of territorial restructuring in a steadily globalizing world by focusing on urban megaproject development. Contributions focus on the principal actors, institutions, and innovations that drive capitalist globalization, socio-economic and territorial restructuring, and global city formation by exploring the architectural design, planning, management, financing and impacts of urban megaprojects as well as their various socio-economic, political and cultural contexts. This is the first work on urban megaprojects to be global in scope, with chapters about Korea, Bilbao, Kuala Lumpur, Budapest, Milan, Abu Dhabi, New York, Paris, Sao Paulo, Beijing, Shanghai, Hamburg, Vienna, Detroit, Philadelphia, Stuttgart, Afghanistan and Mexico City. It is also the first work on the subject to include contributions from sociologists, planners, geographers and architects from top universities around the world, thus making it a truly multidisciplinary project.
Includes index.
Keywords: Social Science -- Sociology -- Urban.; Social Science -- Human Geography.; Architecture -- Urban & Land Use Planning.; Sociology.; Urban & municipal planning.; City planning.; Project management.; elektronické knihy; electronic books